Aplikasi Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) Pada Nata De Coco Dalam Menurunkan Kadar Kolesterol Total, LDL, Dan Meningkatkan HDL Pada Mencit (Mus musculus) - Theopilus Wilhelmus Watuguly; Anik Uniarti; Maria Nindatu (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2019)
Hypercholesterolemic sufferers generally consume conventional drugs using hypolipidemic drugs to reduce cholesterol levels. But this type of drug also has side effects. In addition to consuming hypolipidemic drugs, increased cholesterol levels can be suppressed by regulating dietary patterns by controlling nutrient intake in a balanced manner as needed. Red dragon fruit skin extract (Hylocereus polyrhizus) applied to nata de coco is believed to reduce cholesterol levels because both contain fiber which can be used for dietary needs, and improve the digestive process. The purpose of this study was to determine the application and determine the dose of red dragon fruit skin extract (Hylocereus polyrhizus) in nata de coco in reducing total cholesterol, LDL and increasing HDL in mice (Mus musculus). The type of research used is experimental research using the Pre-Post Test Only Control Group Design research design that uses 18 mices with different doses of 1: 1 and 1: 2 doses. ANOVA statistical test on the results of the study showed that effective treatment in reducing total cholesterol, LDL, and increasing HDL was treated with extracts of red dragon fruit skin (Hylocereus polyrhizus) in a 1: 2 nata de coco. Thus it can be concluded that the higher the dosage given to mice tested it showed a significant reduction in cholesterol levels.